Raised up west side [videorecording (DVD)] : change the narrative and change lives (Freestyle, 2023)
Chicago's West Side epitomizes the violent, struggling city we see daily in the media. It peels back the layers, exposing the deep-seated segregation, food insecurity, and mass incarceration that continue to shape these predominantly Black neighborhoods. Following the harrowing, yet frequently inspiring plight of ex-offenders, social activists, and entrepreneurs working on the West Side, we witness the fierce tenacity required to change the narrative and change lives.